Pemanfaatan Artificial Intelligence Sebagai Apologetika Digital di Era Postmodern Menurut Kisah Para Rasul 17:16–34 - Samuel Sampelan; Ineke Tombeng (Jurnal Teologi Pambelum, 2026)
The development of Artificial Intelligence (AI) in the postmodern era has brought significant implications for human life, particularly in social, ethical, and theological dimensions. One major challenge emerging within digital spaces is the dissemination of doctrinal deviations, including the reduction of Scripture to a mere moral guide, interpretations of salvation that emphasize human effort apart from grace, the relativization of biblical authority as one source of truth among many competing narratives, and the blending of Christian faith with popular spirituality and postmodern ideologies. This article examines the use of AI in the development of digital apologetics by drawing on the apologetic strategy of the Apostle Paul in Athens as recorded in Acts 17:16–34. Employing a hermeneutical approach and contextual theology, this study demonstrates that Paul’s emphasis on rational dialogue, cultural sensitivity, and clear theological proclamation provides a conceptual model for the church in addressing contemporary digital challenges. While AI operates through the aggregation of diverse sources and narratives and thus risks equating Scripture with personal experience, popular culture, and non-Christian spirituality as equal authorities, it can also serve to strengthen faith formation and expand the public witness of the Gospel when grounded in divine revelation and guided by the Holy Spirit. Consequently, digital apologetics in the postmodern era is not merely a reactive defense of faith but a transformative practice that affirms God’s presence as the ultimate source of wisdom and truth in a digitalized world.